Equatorial Atlantic hydrographic and seawater sensor data collected during RRS James Cook cruise JC094 (processed ROV 1m depth bins downcast) - Robinson, Laura F (PANGAEA, 2023)
This data release includes sensor data collected from Remotely Operated Vehicle (ROV) sensors during a 2013 (October - November) research expedition onboard the RRS James Cook, JC094, in the Equatorial Atlantic Ocean. The JC094 TROPICS cruise was a fieldwork component of a European Research Council funded project, CACH ('Reconstructing abrupt Changes in Chemistry and Circulation of the Equatorial Atlantic Ocean: Implications for global Climate and deep-water Habitats') led by Prof. Laura Robinson from the University of Bristol to study paleoclimate archives in the Atlantic. Seventeen ROV dives were carried out. All downcast data have been binned by depth (1m intervals).